Knowledge, Attitude and Practice on Physical Activities among Undergraduate Medical Students of Devdaha Medical College Teaching Hospital - Sharma, Shanta; Dhakal, Indra; Chalise, Satkar (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Physical activities are one of the major contributors to one’s physical ﬁtness and health. Physical activities are known to prevent many globally leading non-communicable diseases. Medical students are even taught in their curriculum about these diseases and the role of physical activities in their prevention. They might be adopting different types of physical activities in their daily life and some might be ignoring or being deprived of practicing physical activities due to various reasons. MATERIAL AND METHODS A descriptive cross-sectional study using pre designed questionnaire was conducted among ﬁrst to ﬁnal year medical students of Devdaha medical college to assess knowledge, attitude and practice on physical activities where 162 students were selected purposively and thus obtained data were analyzed using IBM SPSS version 24. RESULTS Majority of the students had a good knowledge of physical activity and a positive attitude towards physical activities. Most of them (97.67%) have performed physical activities in their life and a majority of them (79.07%) were currently involved in physical activities. Cardio training was the most practiced physical activity followed by sports and yoga practices. Lack of company and lack of time were identiﬁed as factors abstaining physical activities among them who left practicing physical activities. CONCLUSION This study was done to explore knowledge, attitude and practice on physical activities of medical students. The majority of the students had a good knowledge regarding beneﬁts of physical activities, and positive attitude towards physical activities, however only a moderate number of students practiced physical activities.